Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

In a text that I am reading, they state that the following partial fraction ($r$ fixed) expansion is "readily computed":

$$f(z) = \frac{z^r}{(1-z)(1-2z)(1-3z)\cdots (1-rz)} = \frac{1}{r!} \sum_{j=0}^r \binom rj \frac{(-1)^{r-j}}{1-jz}$$

I know how to do partial fractions, or at least I thought I did. I tried to set it up with something like $$\frac{A_1}{1-z} + \frac{A_2}{1-2z} + \cdots + \frac{A_r}{1-rz}$$ but it got messy. Also, the answer given above has a constant term $\frac{(-1)^{r}}{r!}$ when $j=0$, which shouldn't show up when doing this method normally.

Could someone point me in the right direction? Thanks!

I now see why the constant term is necessary; doing a "long division" would result in the $\frac{(-1)^r}{r!}$ term. The remainder would be something like $$\frac{z^r - \frac{1}{r!}(1-z)(1-2z)\cdots(1-rz)}{(1-z)(1-2z)\cdots(1-rz)}$$ which technically could be solved by partial fractions...

Induction also looks promising, as suggested by Maesumi.

share|cite|improve this question
The first thing to do is to convince ourselves that this equation produces correct results. When $r = 1$, we have $z/(1-z) = -1/(z-1)-1$. When $r = 2$, we have $z^2/((1-2 z) (1-z)) = -1/(2 (2 z-1))+1/(z-1)+1/2$ $\ldots$. Notice that in both cases we have a constant. Use the Summation and make sure you get the same thing as I used another approach. Next, are you trying to derive or prove the result? – Amzoti May 26 '13 at 21:43
The constant term is necessary because power of numerator and denominator are equal to $r$. Saying it is "readily computed" could be author's humor! So don't feel bad if it is not obvious. Have you tried induction? – Maesumi May 26 '13 at 21:53
Try to use the formula I introduced in this problem. – Mhenni Benghorbal Jun 17 '13 at 20:58

The coefficient of $\frac{1}{1-kz}$ is $$\left[\frac{z^r}{(1-z)(1-2z)(1-3z)\cdots\widetilde{(1-kz)}\cdots (1-rz)}\right]_{r=\frac{1}{z}}=\frac{\left(\frac{1}{k}\right)^r}{(1-\frac{1}{k})(1-2\frac{1}{k})(1-3\frac{1}{k})\cdots\widetilde{(1-k\frac{1}{k})}\cdots (1-r\frac{1}{k})}=\frac{1}{k(k-1)(k-2)\cdots\widetilde{0}(-1)(-2)\cdots(k-r)}=\frac{1}{r!} \binom rj (-1)^{r-j}$$

share|cite|improve this answer

Multiply by $\frac{1}{1-jz}$ and plug in $\frac{1}{j}$ to get \begin{align*} A_j&=\frac{1/j^r}{\left( 1-\frac{1}{j} \right)\left( 1-\frac{2}{j} \right)\cdots \left( 1-\frac{j-1}{j} \right)\left( 1-\frac{j+1}{j} \right)\cdots \left( 1-\frac{r}{j} \right)} = \\ &= \frac{1}{j\left( j-1 \right)\left( j-2 \right)\cdots \left( j-j+1 \right)\left( j-j-1 \right)\cdots \left( j-r \right)}= \\ &= \frac{1}{\underbrace{j\left( j-1 \right)\left( j-2 \right)\cdots 1}_{j!} \cdot \underbrace{(-1)(-2) \cdots (-(r-j))}_{(-1)^{r-j}(r-j)!}}= \\ &= \Big\{\binom{r}{j} = \frac{r!}{j!(r-j)!}\Big\}= \frac{1}{r!}\binom{r}{j}\left( -1 \right)^{r-j} \end{align*}

By polynomial division, we can write \begin{equation} \frac{z^r}{(1-z)(1-2z)\cdots (1-rz)}=q+\frac{c}{(1-z)(1-2z)\cdots (1-rz)}\tag{1} \end{equation} where $q, c\in \mathbb{R}$. By theory of partial fractions, we can have at most $r$ fractions, so by the above, we get \begin{equation*} \frac{c}{(1-z)(1-2z)\cdots (1-rz)}=\sum_{j=1}^{r}\frac{A_j}{1-jz} \end{equation*} Plugging in $0$ in (1), we thus obtain \begin{align*} q=A_0&=-\frac{1}{r!}\sum_{j=1}^{r}\binom{r}{j} \frac{(-1)^{r-j}}{1-0}= \\ &=-\frac{1}{r!}\Big[\underbrace{\sum_{j=0}^{r}\binom{r}{j}(-1)^{r-j}}_{(1-1)^r=0}-\binom{r}{0}(-1)^r \Big]=\frac{(-1)^r}{r!} \end{align*}

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.